ENGLISH CLUB: A MEDIUM FOR LANGUAGE LEARNING AND ACQUISITION - Husniya, Asiyatul (Journal Cerdas Mahasiswa, 2023)
Teaching and learning in the 21st century is full of challenges and opportunities, especially when teaching students for whom English is a new language. Teacher teaching strategies are one of the causes of language difficulties. Therefore, English club as extracurricular was formed to overcome the problems. This research aims to explain the way of teacher teaching speaking in English club at SMAN 1 Tanjung Raya. Qualitative method with case study approach was used in this journal. The researcher used observations, interviews and documentation to answer the formulation of research. Observations were made during the implementation of activities in English. Then, interviews have also been conducted to teachers and students involved in the English club. The trustworthiness of the data was obtained by using triangulation technique. The last, was documentation to support statement above. This research found that teachers take optimized approach to be closer and open with students. Students become more comfortable because united by a community of learners who have the same goal of improving English language skills. Overall, the idea highlights the effectiveness of English clubs as a dynamic and engaging medium for language learning and acquisition, emphasizing the practical application of English in real-life contexts among learners.